UTILIZATION OF ARTIFICIAL INTELLIGENCE SYSTEMS TO PREDICT CONSUMER BEHAVIOR - zaenal aripin; Lili Adi Wibowo; Maya Ariyanti (Journal of Jabar Economic Society Networking Forum, 2023)
The development of Artificial Intelligence (AI) System technology has opened up new opportunities in understanding consumer behavior. With abundant data availability, companies have the potential to improve marketing and customer service strategies through predicting consumer behavior. This study aims to explore the implications of utilizing Artificial Intelligence Systems in predicting consumer behavior and its impact on business strategies. The purpose of this study is to identify the benefits of utilizing Artificial Intelligence Systems in predicting consumer behavior, analyze challenges that may arise, and detail strategies that companies can adopt to optimize the utilization of this technology. The research method used is a combination of literature analysis and case studies. Literature analysis was conducted to detail the theoretical basis regarding the utilization of Artificial Intelligence Systems in the prediction of consumer behavior. Case studies were conducted on a number of companies that have successfully implemented this technology to understand the context of their implementation and the benefits they derived. The results showed that the utilization of Artificial Intelligence Systems in predicting consumer behavior can improve service personalization, optimize marketing strategies, and provide deep insights into consumer preferences. However, challenges related to data privacy, ethics, and technology integration are still obstacles that need to be overcome. Strategies that focus  on data security, transparency, and an ethical approach can help companies address these challenges.